Le Remix comme forme littéraire : essai sur les publications récentes de Caroline Bergvall - Vincent Broqua (Sillages Critiques)
Recent publications by poet and artist Caroline Bergvall shift the old paradigm of both the poetry collection and the book-poem. This shift can be analyzed with the notion of “remix” that Lev Manovich uses to characterize new media. Bergvall’s recent books (Meddle English and Drift) are remixes in terms of their structure, of their individual texts, but above all in terms of their remediation as podcasts, performances, shows, printed material. They anticipate the “remixability” of her most recent projects subsumed under the title Sonic Atlas. But Bergvall’s remixability is not formal or technological, it is a poetics and a politics of multiplicity that seeks to define how to live together now.